Index and Recognition for the Shape Contour of Plant Leaves - Xun Liu; Keyi Hou; Liliang Wang; Ping Liu (2009 WRI Global Congress on Intelligent Systems, 2009)
Content-based image retrieval methods are used to construct systems to retrieve and classify plants' leaves. The target of this paper is to balance matching veracity and computing efficiency and to improve the process of extracting feature. This paper focuses on the shape feature of the image. The work we have finished includes in the process of choosing feature and using numerical sequence of image features to solve the question about the irrespective of image featurepsilas circumrotating transformation. In the design process, we adopt general content-based image retrieval framework. So, result of this paper is used to plant leavespsila classifying and recognizing.